Application of Analytic Hierarchy Process (AHP) in Selecting the Best Employee: Comparing and Integrating Public and Private Organizations’ Approaches in the Framework of Reward and Multi-Criteria Decision Making - Khaledian, Samad; Motamedi, Hamidreza; Fanaei Niya, Omid; Goodarzi, Hamid; Mirzaei, Mahdi; Jahanshahi, Ramin (International journal of Modern Achievement in Science, Engineering and Technology, 2026)
Selecting the best employee, as one of the fundamental challenges of human resource management, plays a decisive role in improving productivity and achieving organizational goals. In competitive environments of the private sector and bureaucratic structures of the public sector, this process is often accompanied by bias and subjective judgments. The present study, by integrating the two approaches presented in the studied articles, examines the application of the Analytic Hierarchy Process (AHP) method in selecting the best employee. The main issue is the need for a scientific and transparent framework for multi-criteria evaluation that can simultaneously consider hard criteria (education, experience, technical skills) and soft criteria (honesty, responsibility, innovation, organizational cultural values). The importance of this issue lies in its ability to reduce bias, create healthy competition, and support the employee reward and motivation system. The structure of the research includes a literature review, explanation of the AHP steps, comparison of its application in the public and private sectors, and presentation of an integrated model. The research findings show that AHP, using pairwise comparison, calculation of relative weights, and sensitivity analysis, enables objective and reliable selection of the best employee. The results indicate that the proposed integrated model can be used both in government organizations to strengthen the reward system and in private companies to improve productivity.